Studi Kelayakan Bisnis Pada Usaha Susu Kambing Ettdjawa Farm di Purwokerto - Alvi Izzatin Aghnisia Putri; Alvian Septiningsih; Amalia Nurul Fajriyah; Indah Pita Pratama; Nandha Cantika; Riva Ady Saputra; Sely Nur Anjani; Tariska Dina Aulina; Sudiro (CV. ITTC INDONESIA, 2026)
This study aims to analyze the marketing and management aspects of the Ettdjawa Farm Goat Milk Center in Purwokerto using a business feasibility study approach. The research employed a qualitative descriptive method, and data were collected through observations and interviews. The findings reveal that marketing strategies are carried out through direct marketing (door-to-door) and social media promotion. These strategies have been effective in introducing goat milk products, increasing consumer trust, and expanding market reach. In terms of management, the business is operated independently and uses a simple management system covering production processes, livestock maintenance, human resource management, and environmental management. Despite its simple operations, the business has maintained product quality and utilized livestock waste as organic fertilizer that benefits the surrounding community. Therefore, Ettdjawa Farm demonstrates strong potential and is feasible for further development through improved marketing strategies and optimized business management